UMPSA students foster volunteerism by participating in Bakti Madani programme - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 21 February 2025 – A total of 50 students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) are participating in the Bakti Madani Programme, which runs from 21 to 24 February. The Official Opening Ceremony of the Bakti Madani programme was officiated by the Member of Parliament for Pekan, Dato’ Sri SH Mohmed Puzi SH Ali. Also present were the Deputy Vice-Chancellor (Student Affairs & Alumni), Professor Ts. Dr. Mohd Rusllim Mohamed, the Deputy Vice-Chancellor (Academic and International Affairs), Professor Dato’ Ir. Ts. Dr. Ahmad Ziad Sulaiman, and a representative from the Student Affairs Division, Ministry of Higher Education Malaysia, Muhammad Najmi Marcelo Abdullah.